Comparative morphology of the mandibulodental complex in wild and domestic canids. - Kieser, J A (1992)
The relationships between mandibular and dental measurements were investigated in a sample of 60 adult domestic dogs, 17 black-backed jackals Canis mesomelas, 18 side-striped jackals C. adustus and 16 Cape foxes Vulpes chama. Standard mesiodistal and buccolingual tooth measurements, together with 8 mandibular measurements (intercondylar distance, intercarnassial breadth, mandibular length, arch length, condylar height, canine-condylar length, mandibular width, mandibular height) were scaled allometrically to total skull length. Despite wide differences in diet and sexual dimorphism between the 3 wild canid species, larger canids were found to be scaled up versions of smaller canids. While males showed a highly concordant patterning when compared with domestic dogs of equivalent size, females showed a remarkably mosaic pattern. Relative to skull size, the only teeth that appear to be larger than those of equivalently sized domestic dogs were the second molars. It is suggested that those theories of sexual dimorphism and functional integration which apply to skeletodental dimensions in primates may not be applicable to canids.